Self-turning PID Control design - Jamaluddin, Hishamuddin (Penerbit UTM, 2007)
Most of engineering systems today are dependent on automatic control rather than manual control. This is because automatic control has practical advantages compared with manual control. It is wrong morally to use human to carry a heavy work and expose them to threat of safety and continuous working. These works are more suitable for machines that require automatic control system. Some reasons by automatic control systems are preferred: 1. Human have a time delay reaction of about 0.3s. 2. A continuous work over long period and complex movement will cause pressure and consequently affect human’s attitude. 3. It is possible to repeat standard human movement using mechanisms. 4. In most applications, operators may be exposed to dangerous environment, such as radiation, and long repetitive jobs. A controller is the bread and butter of a control system in which control action is generated and used as input to the system. One of the most commonly used and famous controller is the Proportional-Integral-Derivative (PID) controller. The PID controller is by far the most common control algorithm and is being used extensively in industries to control most feedback loops.